Adaptación al conflicto entre paradigmas interpretativos en el contexto del cambio cultural: negación, disfraz y discursos transicionales - Xavier Ricard Lanata (Journal de la Société des Américanistes)
Adaptation to conflict among interpretative paradigms in contexts of cultural change: denial, disguise and transitional discourses. The analisis of belief systems, within contexts of cultural transformation and conflict among religious discourses and practices mutually incompatible, requires new conceptual and methodological tools, that could provide us with an account of the complexity and unstability of religious phenomena. Drawing from a study of religious discourses and practices existing among contemporary shepherds of the Ausangate cordillera (Southern Peruvian Andes), we will distinguish three strategies allowing an adaptation to religious conflict. The notion of « transitional discourse » in particular helps to understand a mode of combining paradigms in contexts of social pressure. This will lead us to establish a preliminar frame for religious conflict analisis, and for an « anthropology of the subject » sensitive to subjective processeses of appraisal and legitimation of interpretative paradigms.